2018
DOI: 10.1080/09687637.2018.1478949
|View full text |Cite
|
Sign up to set email alerts
|

“I think we should all be singing from the same hymn sheet” – English and Swedish midwives’ views of advising pregnant women about alcohol

Abstract: "I think we should all be singing from the same hymn sheet"-English and Swedish midwives' views of advising pregnant women about alcohol Many countries have adopted abstinence guidelines for pregnant women, due to uncertainty around the risk of harm caused by small amounts of alcohol. There is a lack of research exploring frontline midwives' attitudes towards alcohol use during pregnancy and comparisons of practices in different countries. Sixteen semi-structured interviews were conducted with midwives working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…However, as the findings demonstrated, practitioner support can be limited [ 30 , 39 , 42 , 43 , 45 , 50 , 53 , 55 ]. Conflicting information from the media and evolving guidelines can influence practitioners to doubt their overall abstinence or alcohol reduction messaging [ 15 , 65 ]. It can result in confusion, mixed messaging, and misinformation among those who wish to know more about alcohol use in pregnancy [ 29 , 30 , 39 , 40 , 42 , 43 , 45 , 46 , 48 , 50 , 51 , 53 , 54 ].…”
Section: Discussion and Application Of The Stigma Action Frameworkmentioning
confidence: 99%
“…However, as the findings demonstrated, practitioner support can be limited [ 30 , 39 , 42 , 43 , 45 , 50 , 53 , 55 ]. Conflicting information from the media and evolving guidelines can influence practitioners to doubt their overall abstinence or alcohol reduction messaging [ 15 , 65 ]. It can result in confusion, mixed messaging, and misinformation among those who wish to know more about alcohol use in pregnancy [ 29 , 30 , 39 , 40 , 42 , 43 , 45 , 46 , 48 , 50 , 51 , 53 , 54 ].…”
Section: Discussion and Application Of The Stigma Action Frameworkmentioning
confidence: 99%
“…Engagement with women to promote health is in line with the public health role of the midwife in the UK and internationally [46][47][48]. Reassuringly, professional role and identity was a strong enabler of advising abstinence at antenatal appointments other than booking, indicating that midwives see advising women to abstain as part of their role and that it is expected of them and that they have intentions to do so.…”
Section: Discussionmentioning
confidence: 96%
“…Midwives tend to support the contention that women are 'confused' by messages from different sources providing variable advice and that a clear, unambiguous message is the preferred option However, very often midwives are reluctant to advise total abstinence as they are aware of the lack of good evidence for that message or feel that small amounts do no harm (Van der Wulp, 2013;Schölin et al 2018;Crawford Williams et al, 2015).…”
Section: Delivering the Message -Caught Between Professional 'Dictates' And Real Lifementioning
confidence: 99%
“…In a study comparing English and Swedish midwives, it was generally felt that, '…we should all be singing from the same hymn sheet' regarding delivering an abstinence message (Schölin et al 2018, p.5), and that any drinking during pregnancy could indicate an underlying alcohol problem. Comparing the risk discourses of the nine Swedish and seven English midwives interviewed, Schölin et al (2018) reported that English midwives' views were quite nuanced and the uncertainty around the risk of drinking small amounts was mentioned. By contrast, Swedish midwives' risk discourse was binary: either women stop drinking or they continue because they have an underlying drinking problem.…”
Section: Delivering the Message -Caught Between Professional 'Dictates' And Real Lifementioning
confidence: 99%